EVALUATION OF SAFETY AND EFFICACY OF PHARMACOLOGICAL AND NON-PHARMACOLOGICAL TREATMENTS USED BY IRRITABLE BOWEL SYNDROME PATIENTS - Sarhan, Reem (An-Najah National University, 2024)
Background: Many people in Palestine suffer from irritable bowel syndrome (IBS). Some people deal with the disease using medications, while others prefer non-pharmacological treatments and avoid food that aggravate the symptoms. Objectives: The study aims to assess the severity of IBS, the lifestyle the patients live and evaluate the safety and efficacy of pharmacological and non-pharmacological modalities to treat irritable bowel syndrome among Palestinian patients. Methodology: This was a cross-sectional study using a data collection form to collect data from patients by a face-to-face interview. Patients were met from gastroenterology outpatient clinics, community pharmacies and hospital pharmacies in Bethlehem. The Statistical Package for Social Sciences was performed using statistical analysis (SPSS version 21). Results: A total of 407 patients with irritable bowel syndrome in Bethlehem and surrounding areas participated in this study. The mean age was 36.87±13.8 years old. Among them, 253(62.2%) were females, 263(64.6%) were married and 201(49.4%) were living in the city. Regarding clinical and disease characteristics, 258(63.4%) did not have a family history of IBS, 201(49.4%) had alternate diarrhea and constipation, 229(56.3%) had mixture of solid and watery stool, 310(76.2%) had abdominal pain, 352(86.5%) had abdominal bloating, 350(86%) had abdominal gases, and 69(17.0%) had a bloody stool. Furthermore, the disease affected patients’ life by different ways; 248(60.9%) became nervous, 129(31.7%) couldn’t sleep well. Regarding non-pharmacologic treatments, 206(75.2%) used herbs to sooth IBS symptoms, and 234(57.5%) avoided food that irritates colon. It was found that using herbs that sooth the IBS, increasing liquids, avoiding food that irritates the colon and having exercise were all significantly associated with improvement in IBS symptoms; P-values were <0.001, 0.032, 0.001 and 0.029 respectively. About pharmacologic treatments, 188(46.2%) had taken chlordiazepoxide and clinidium bromide, and 143(35.1%) had taken probiotics to treat IBS symptoms. 148(36,4%) patients told that they had full improvement from pharmacological treatments. Use of probiotics, synthetic fibers, (chlordiazepoxide & clinidium bromide) and hyoscain significantly associated with improvement in symptoms, P-values were <0.001, <0.001, <0.001 and 0.030 respectively Conclusion: Irritable bowel syndrome is a bothering problem that affects daily life, many patients try non-pharmacological treatments with accepted efficacy. Even with pharmacological treatments many patients could not attain satisfactory improvement
تقييم سلامة وفعالية العلاجات الدوائية وغير الدوائية المستخدمة من قبل مرضى متلازمة القولون العصبي